A single amino acid substitution in the FAD-binding domain causes the inactivation of Propionibacterium Acnes isomerase. Issue 4 (2nd April 2020) - Rao, Yu; Li, Shi-Li; Li, Mei-Juan; Cui, Sheng; Gou, Ke-Mian
ABSTRACT: We previously demonstrated the efficient production of trans 10, cis 12-conjugated linoleic acid (t10c12-CLA) in Lactococcus lactis by ectopically expressing a Propionibacterium acnes isomerase (pai) gene and also mentioned that a recombinant strain was unable to accumulate t10c12-CLA product, despite the normal transcription. Here, the molecular analysis indicated that this mutated strain harbors a pai gene with a single-nucleotide mutation converting GC 50 A to GTA, leading to a corresponding change of Alanine residue into Valine. The expression of the reverse mutation resulted in the recovery for enzyme activity. Site-directed mutagenesis indicated that the codon usage of Val 17 was not responsible for the enzyme inactivation in the Ala 17 Val mutation. Western blot analysis revealed that the recombinant PAI protein was not detectable in the His tag-marked Ala 17 Val mutant. It is, therefore, reasonable to assume that Ala 17 residue is critical for PAI functionality. Abbreviations: pai: propionibacterium acnes isomerase; CLA: conjugated linoleic acid; t10c12-CLA: trans 10, cis 12-CLA; LA: linoleic acid (18:2n-6); FAD: flavin adenine dinucleotide Graphical abstract: : The Ala-17 residue is critical for PAI enzymic activity.